Granulometric and facies analysis of Middle–Upper Jurassic rocks of Ler Dome, Kachchh, western India: an attempt to reconstruct the depositional environment - Ghaznavi, Asma A.; Quasim, M.A.; Ahmad, A.H.M.; Ghosh, Sumit K. (Geologos, 2019)
Grain size analysis is an important sedimentological tool used to unravel hydrodynamic conditions, mode of transportation and deposition of detrital sediments. For the present study, detailed grain size analysis was carried out in order to decipher the palaeodepositional environment of Middle–Upper Jurassic rocks of the Ler Dome (Kachchh, western India), which is further reinforced by facies analysis. Microtextures were identified as grooves, straight steps and V-shaped pits, curved steps and solution pits suggesting the predominance of chemical solution activity. Grain size statistical parameters (Graphic and Moment parameters) were used to document depositional processes, sedimentation mechanisms and conditions of hydrodynamic energy, as well as to discriminate between various depositional environments. The grain size parameters show that most of the sandstones are medium- to coarse-grained, moderately to well sorted, strongly fine skewed to fine skewed and mesokurtic to platykurtic in nature. The abundance of medium- to coarse-grained sandstones indicates fluctuating energy levels of the deposition medium and sediment type of the source area. The bivariate plots show that the samples are mostly grouped, except for some samples that show a scattered trend, which is either due to a mixture of two modes in equal proportion in bimodal sediments or good sorting in unimodal sediments. The linear discriminant function analysis is predominantly indicative of turbidity current deposits under shallow-marine conditions. The C-M plots indicate that the sediments formed mainly by rolling to bottom suspension and rolling condition in a beach subenvironment. Log probability curves show that the mixing between the suspension and saltation populations is related to variable energy conditions.